2021
DOI: 10.2147/idr.s307683
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Wet Mount and Concentration Techniques of Stool Examination for Intestinal Parasites Identification at Debre Markos Comprehensive Specialized Hospital, Ethiopia

Abstract: Background Intestinal parasitic infection has serious medical and public health impacts in developing countries. Intestinal parasites were under reported via direct wet mount method due to its poor sensitivity. So, the selection of a more sensitive and reliable diagnostic method is essential. Objective The aim of the study was to evaluate the diagnostic performance of wet mount and concentration techniques of stool examination for intestinal parasites identification. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
1
12
0
1
Order By: Relevance
“…Our study findings illustrated that the direct wet mount method had very low sensitivity (5.6%) for the diagnosis of trichostrongylosis compared to the other parasitological methods. This is similar to other studies, which demonstrated that the direct wet mount method had a low detection ability for intestinal helminthic infections and may lead to false-negative results ( Mengist et al., 2018 ; Demeke et al., 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…Our study findings illustrated that the direct wet mount method had very low sensitivity (5.6%) for the diagnosis of trichostrongylosis compared to the other parasitological methods. This is similar to other studies, which demonstrated that the direct wet mount method had a low detection ability for intestinal helminthic infections and may lead to false-negative results ( Mengist et al., 2018 ; Demeke et al., 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…Stool samples will be collected using stool cups and stored in 10% formalin to preserve the parasite until analysis. 34 A portion of each stool sample will be used to detect direct ova, larvae and cysts of intestine parasites using formal ether concentration technique. 35 Urine samples will be collected from WRA and school-age children using 60 mL urine cup containers.…”
Section: Discussionmentioning
confidence: 99%
“…The pellet underwent direct wet smear, xenic cultivation, Ziehl-Neelsen's (ZN) staining, floatation and McMaster techniques to recover and quantify the organisms. Direct wet mount was used mainly for protozoa trophozoites [27]. A small amount of concentrated water pellet was put on a microscope slide, and a drop of iodine was added.…”
Section: Laboratory Analysismentioning
confidence: 99%